Secondary Adult Education and the Sustainable Development Goals: Reflections and experiences of a teacher in Andalusia, Spain - Najarro-Martín, Ulises (2025)
This article invites reflection and raises the following question: is there an integration of the SDGs in the curriculum and educational practices of adult secondary education in Andalusia (Spain), can the SDGs be effectively integrated into adult education, and what impact does their integration have on the learning and development of this type of students? These questions will be addressed from the real knowledge of the curriculum and from the teaching experience in Secondary Adult Education in Andalusia (Spain) through the subject of Social Sphere. The main conclusion is that the integration of the SDGs in educational practices contributes to generate significant learning in adult learners, enabling them to face global challenges and contributing to the formation of a sustainable global citizenship.